Age-specific MRI brain and head templates for healthy adults from 20 through 89 years of age - Fillmore, Paul T.; Phillips-Meek, Michelle C.; Richards, John E. (Frontiers in Aging Neuroscience, 2015)
This study created and tested a database of adult, age-specific MRI brain and head templates. The participants included healthy adults from 20 through 89 years of age. The templates were done in 5-year, 10-year, and multi-year intervals from 20 through 89 years, and consist of average T1W for the head and brain, and segmenting priors for GM, WM, and CSF. It was found that age-appropriate templates provided less biased tissue classification estimates than age-inappropriate reference data and reference data based on young adult templates. This database is available for use by other investigators and clinicians for their MRI studies, as well as other types of neuroimaging and electrophysiological research (http://jerlab.psych.sc.edu/NeurodevelopmentalMRIDatabase/).